A Bayesian Network Perspective on an Attributional Model of Reactions Toward People with HIV - Brandelli Costa, Angelo (2023)
Objective. Attributional theory has been widely studied to understand the overall perceptions regarding people suffering from negative events such as an HIV infection. The aim of the present study is to test the overall attribution model and its influence on the willingness to help, considering emotional reactions related to an HIV-infected individual. Method. We used a Bayesian network to analyze the association between attributions of causality (blame, responsibility, and control), willingness to help, and emotional reactions (anger and sympathy) toward an HIV-infected patient. Three hundred and fifty-eight individuals participated in the study. Results. Using the overall model, we found two different results: Anger contributed to the cognitive processes of attribution, and sympathy contributed to the behavioral willingness to help the patient.